Perbandingan Antara Perkembangan Kinerja Ekonomi Daerah Otonomi Baru dan Daerah Induk di Indonesia Pasca Pemekaran - Yumanda, Friska Cahya; Aminy, Adhinda Rachma (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2023)
This study aims to compare the development of economic performance between the parent region and the new autonomous regions after the division. The research sample consists of 27 regions, including 14 new autonomous regions (DOB) and 13 parent regions (DI) which are affected areas from the expansion carried out during the period 2012 and 2013. The research sample uses data from 2014-2018, which is data from the first five year available after the expansion. The research uses the non-parametric Mann-Whitney test by comparing the mean rank values between the DOB and DI groups annually through the t-test. As a result, it is known that the new autonomous regions have developed a level of regional financial capacity, a level of regional independence, and a level of dependence on transfer funds that are better than the parent region. On the other hand, the growth of GRDP per capita and the poverty rate in the new autonomous regions show worse performance than the parent regions.